Deep Oxidative Desulfurization of Model fuels by Prepared Nano TiO2 with Phosphotungstic acid (Journal of Engineering, 2018)
In this study, nano TiO2 was prepared with titanium isopropoxide (TTIP) as a resource to titanium oxide. The catalyst was synthesized using phosphotungstic acid (PTA) and, stearyl trimethyl ammonium bromide (STAB) was used as the structure-directing material. Characterization of the product was done by the X-ray diffraction (XRD), X-ray fluorescent spectroscopy (XRF), nitrogen adsorption/desorption measurements, Atomic Force Microscope (AFM) and Fourier transform infrared (FTIR) spectra, were used to characterize the calcined TiO2 nanoparticles by STAB and PWA. The TiO2 nanomaterials were prepared in three crystalline forms (amorphous, anatase, anatase-rutile). The results showed that the nanoparticles of anatase TiO2 have good catalytic oxidative activity. This is because of the conversions of 100% within 90 sec from 300 ppm of dibenzothiophene. This is compared to conversion rates for anatase–rutile nanoparticles and amorphous nanoparticles which reached 52% and 31 %, respectively. The influence of the temperature of reaction, catalyst amount, H2O2 concentration, and initial DBT concentration on the oxidation of DBT was investigated.